El escenario socioecológico del sistema lagunar costero de Mandinga, Veracruz, México: problemas y conflictos en torno a la conservación ante el avance inmobiliario - Ciprés-Chávez, Adrián (2025)
The Mandinga Coastal Lagoon System (MCLS) is in central Veracruz, Mexico. Over the last two decades, an ambitious development project named the Riviera Veracruzana has been implemented, aggravating existing socio-ecological problems. The study analyzed the socio-ecological scenario in this system, characterizing the socio-ecological problems and the social actors involved based on their perceptions, interests and power relations. A two-track methodological scheme was used: (1) collection of information from secondary sources associated with the MCLS and (2) ethnographic data collection with primary sources through semi-structured interviews with key social actors from different social sectors, participatory workshops with focus groups and a field diary. The results revealed a perception of high environmental degradation, socio-ecological conflicts surrounding the conservation and use of territory, and an asymmetry of power among social actors. It is crucial to search for alternatives aiming at power reconfiguration but especially based on people centered, co-produced conservation strategies.